Public relations officers and journalists 1989 - Weibull, Lennart (University of Gothenburg, 1991)
This survey forms part of the project "Publicistisk sed". The questions are divided into six blocks: present and previous employment; functions and occupational role; view of the occupational role of journalists; view of mass media and journalism; view of press ethical rules; background.

Purpose:

Shed light on public relation officers' perception of Swedish journalism and their view of their occupational role and work situation

Denna undersökning ingår i forskningsprojektet "Publicistisk sed". Frågeformuläret var uppdelat i sex frågeområden: arbete och anställningar; arbetsuppgifter och yrkesroll; syn på journalisters yrkesroll; syn på massmedier och journalistik; syn på pressetiska regler; samt bakgrundsfrågor.

Syfte:

Belysa hur svensk journalistik uppfattas bland informatörer samt vilken syn man har på yrkesroll och arbetssituation
Informatörer och journalister 1989
Keywords: Media; Media; Working conditions; Arbetsförhållanden; Social Sciences; Samhällsvetenskap